Assessing The Country’s Legal Framework for Taxing Digital Transactions: A Basis for Recommending Policy Measures - Cater, Belinda P.; Agustin, Reynabeth C.; Josef, Joebel R.; Oxales, Allura Ayo F.; Malang, Bernandino P. (Future Science / FSH-PH Publications, 2023)
This study aims to assess the country’s legal framework for taxing digital transactions. Specifically, the extensiveness of which the provisions of the legal framework can implement the value of digital transactions to taxpayers. This study employs a qualitative method by reviewing and further analyzing relevant case studies, recent gap analysis, policies, and literature on taxing digital transactions, and conducting interviews with policy experts from the Bureau of Internal Revenue (BIR). Recent study recommends enhanced policy measures based on the findings on new digital technology and its possible interactions with both current and proposed tax policies, three (3) policies were recommended. First, optimizing existing authority to tax over online platforms. Second, to have a digital-ready tax administration. Finally, to have an expanded and continued investigation for enhancement and liability regarding these digital transactions. Findings include that the BIR doesn’t have enough systems to capture all revenue-generated digital service providers and is unable to track all revenue-generating digital platforms. The Philippines should continue improving taxing rights and administration pursuant to modern times. This study concluded that digital platforms can be designated as withholding agents, improve communication channels with these digital platforms and tie them up with BIR exclusively for data access, and finally, a centralized BIR portal where all digital service providers will be registered and monitored. This will be the tax platform for online transactions that is convenient and accessible for taxpayers and is deemed a highly resilient revenue generation and imposition of tax administration as time changes.